Comparative morphology of anuran testes - De Oliveira, Classius [UNESP] (2012)
Testes in anurans are a structure that posses distinct morphology and coloration. Spermatogenesis in these group is a complex and organized process that involves spermatogenic cysts progression through in the seminiferous epithelium. The germ cells are grouped with Sertoli cells and constitute spermatogenic cyst. Germ cells are distinct in species of different families. © 2012 by Nova Science Publishers, Inc. All rights reserved.